A highly hindered bithiophene-functionalized dispiro-oxepine derivative as an efficient hole transporting material for perovskite solar cells. Issue 47 (16th November 2016) - Rakstys, Kasparas; Paek, Sanghyun; Sohail, Muhammad; Gao, Peng; Cho, Kyung Taek; Gratia, Paul; Lee, Yonghui; Dahmen, Klaus H.; Nazeeruddin, Mohammad Khaja
Abstract : Dimethoxydiphenylamine-substituted dispiro-oxepine derivativeDDOF has been synthesized using a facile synthetic route and tested in perovskite solar cells as a hole transporting material exhibiting a remarkable PCE of 19.4%. Abstract : Dimethoxydiphenylamine-substituted dispiro-oxepine derivative 2, 2′, 7, 7′-tetrakis-( N, N ′-di-4-methoxyphenylamine)dispiro-[fluorene-9, 4′-dithieno[3, 2- c :2′, 3′- e ]oxepine-6′, 9′′-fluorene] (DDOF ) has been designed and synthesized using a facile synthetic route. The novel hole transporting material (HTM) was fully characterized and tested in perovskite solar cells exhibiting a remarkable power conversion efficiency of 19.4%. More importantly, compared with spiro-OMeTAD-based devices, DDOF shows significantly improved stability. The comparatively comprehensive solid structure study is attempted to disclose the common features of good performance HTMs. These achievements clearly demonstrated that the highly hinderedDDOF can be an effective HTM for the fabrication of efficient perovskite solar cells and further enlightened the rule of new HTM's design.